TOEFL (TEST OF ENGLISH AS A FOREIGN LANGUAGE) TEST PLUGIN UNTUK MOODLE - Leovin Leovin; Ni Made Ary Esta Dewi Wirastuti; Komang Oka Saputra (Jurnal SPEKTRUM, 2022)
TOEFL (Test of English as a Foreign Language) is a test used to measure a person'sEnglish proficiency. Generally, the TOEFL test is used as one of the requirements to graduateat domestic universities, to enter universities abroad, or to work in a country. In this research,the LMS (Learning Management System) was used for implement the TOEFL. LMS is anapplication system that was developed specifically to manage online class (e-learning), andshare subject matter. Moodle (Modular Object-Oriented Dynamic Learning Environment) is anLMS that is usually used in online learning activities. The results of this research that theTOEFL was successfully created as a Moodle plugin and according to the SUS (SystemUsability Scale) test that has been calculated, it got a score of 89, indicating this application hasa high level of feasibility.